Applications of Marine-Derived Microorganisms and Their Enzymes in Biocatalysis and Biotransformation, the Underexplored Potentials - Birolli, Willian G.; Lima, Rafaely N.; Porto, André L. M. (Frontiers in Microbiology, 2019)
The biodiversity has been explored in the search for novel enzymes, including forests, savannas, tundras, deserts and finally the sea. Marine microorganisms and their enzymes are capable of being active in high-salt concentration, large range of temperature and, high incidence of light and pressure, constituting an important source of unique biocatalysts. This review presents studies employing whole cells processes of marine bacteria and fungi aiming new catalysts for different reactions in organic synthesis, such as reduction, oxidation, hydroxylation, hydrolysis, elimination and conjugation. Genomics and protein engineering studies were also approached, and reactions employing isolated enzymes from different classes (oxidoreductases, hydrolases, lyases and ligases) were described and summarized. Future biotechnological studies and process development should focus on molecular biology for the obtention of enzymes with interesting and fascinating properties, as the biocatalyst obtained from the exploration of the microorganisms from the marine environment. This review aims the literature about the use of marine-derived bacteria, fungi and their enzymes for biocatalytic reactions of organic compounds. Promoting a discussion about the possibilities of these microorganisms in the synthesis of different compounds.